Efficacy of Comprehensive Corrective Exercise Program for Upper Crossed Syndrome Among Dental Students- A Cross Sectional Randomized Interventional Trial: Life Sciences-Nursing - T, Murugaraj; R, Hemalatha; N, Sabarish Hariharan; M, Srinivasan; H, Nandini Eshwari; E, Shanmugananth (International Journal of Life Science and Pharma Research, 2023)
Upper cross syndrome (UCS) is a muscle imbalance caused by the weakening and lengthening of the posterior upper back and neck muscles combined with the tightening and shortening of the opposing anterior pectoral chest and neck muscles. The tight muscles are scalene, latissimus dorsi, subscapularis, levator scapula, upper trapezius, sternocleidomastoid, pectorals, suboccipitals, and cervical erectors spinae, and the weak muscles are infraspinatus, deltoid, deep cervical flexors, middle and lower trapezius, serratus anterior, rhomboids, and the supraspinatus. The aim of the present study is to evaluate the effectiveness of comprehensive corrective exercise program (CCEP) for upper cross syndrome among dental students. This study consists of 18 participants of dental students, both male and female, with UCS, aged between 18 and 25 years. They were screened primarily by observation for main factors related to UCS that include altered alignment of postural deviation. The participants were randomized into interventional group, received CCEP for 8 weeks and control group, follow their usual work.: Analysis of Visual Analogue Scale (p<.05), and Reedco scale (p<.05) revealed significant effects. The participants in Interventional Group exhibited greater improvement in terms of pain intensity and posture compared to the participants in control group.: This study showed that the CCEP for people with UCS is achievable and brings about postural change. The CCEP significantly improves the angles of the head forward, shoulder forward, and thoracic kyphosis of dental students.